Evaluation of Three Common Algorithms for Structure Active Control - Sareban, M. (Engineering, Technology & Applied Science Research, 2017)
Recently active structure controllers were considered to deal with the impact of earthquake forces and the result of the investigations provided multiple algorithms to calculate force control and many different ways to apply these forces on the structure. In this study, the efficiency and effectiveness of three methods (linear quadratic regulator, fuzzy logic and pole assigning) are investigated. In addition, three buildings with different height classes with an active tuned mass damper (ATMD) on the top floor are considered to compare the active control methods. Examples with known mass and stiffness and with variable mass are considered. The results show that all three control methods used for the ATMD device reduce the structural response. The fuzzy control method, caused a sharp decline in relative displacement of building floors up to 80%. But in LQR and pole allocation procedures the applied force is limited. The best performance of fuzzy control is for high-rise buildings. The three different methods of control are stable in different masses and even under a random change of floor masses, their effectiveness can be trusted.